2022
DOI: 10.1136/bmjopen-2020-045966
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects on cardiovascular events between use of metformin and dipeptidyl peptidase-4 inhibitors as the first-line hypoglycaemic agents in Japanese patients with type 2 diabetes mellitus: a claims database analysis

Abstract: ObjectivesTo compare the risk of cardiovascular events from the initiation of therapy between metformin and dipeptidyl peptidase-4 inhibitors (DPP-4i) as first-line therapy.DesignRetrospective cohort study using two claims databases.SettingThe MDV database (provided by Medical Data Vision) comprised data from acute care hospitals, and the JMDC database (provided by JMDC) comprised data from individuals covered by health insurance societies.ParticipantsThose who were diagnosed with type 2 diabetes at ≥18 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, a prior clinical trial showed that DPP4i increased the risk of hospitalization for heart failure among older adults with DM [ 40 ], and heart failure may well increase the risk of frailty in this population through multiple mechanisms [ 11 ]. A population-based study compared the cardiovascular risk between metformin and DPP4i users with DM, finding that DPP4i use was associated with a higher risk of cardiovascular events than metformin [ 41 ]. We believe that such excess risk might underly the increasing risk of rising frail severity among these patients in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…However, a prior clinical trial showed that DPP4i increased the risk of hospitalization for heart failure among older adults with DM [ 40 ], and heart failure may well increase the risk of frailty in this population through multiple mechanisms [ 11 ]. A population-based study compared the cardiovascular risk between metformin and DPP4i users with DM, finding that DPP4i use was associated with a higher risk of cardiovascular events than metformin [ 41 ]. We believe that such excess risk might underly the increasing risk of rising frail severity among these patients in the long run.…”
Section: Discussionmentioning
confidence: 99%